PENGARUH EKSTRAK KULIT BATANG ANGSANA (Pterocarpus indicus Willd.) terhadap FEEDING STRTEGY KUMBNG KOKSI (Epilachna punctata Fabricius) - Hidayati, Rahmi; Sumarmin, Ramadhan; Wati, Meliya (STKIP PGRI Sumbar, 2013)
ABSTRACT Ladybird is refers to plant disease found in solanaceae it was able to make big population in short time and damaged the plant for all growing phase. This research purposes to know the effect of Angsana bark Exstract toward feeding stategy of ladybird. This research was using Completely Randomized Design (CRD) 4 treatment and 10 replication. The treatment which gave that was control, the treatment with 2,5 %, 5 %, and 7,5 % concentrated. The data was analyzed by ANOVA and continued by BNT. This research was done in Zoologi Laboratorium of Biologi Department UNP at August 2013. The result of analysis was found that in treatment 2,5 % searching activity koksi of bumblebee needed the fast time was compared with onthers, of grounding activity was found in control for fastest time meanwhile in gathering activity treatment with 5 % concentrated was more effective to bloked the concumn of koksi bumblebee. It ean be conwded that the effect of Angsana Skin Extract 5 % can use as Antifidant and Atractan.